Unique approaches as experiences from some developing countries in promotion of science-technology based economic growth - Long, Hoang Xuan; Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
In the world some developing economies are successful with the objectives to shorten the gap and advance to catch up developed countries in linkage of science-technology and economics such as Korea, Taiwan, China and others. They are countries and territory which apply their own unique approaches with some remarkable points to note such as deviation from and innovative application of theoretical concepts and experiences from developed countries, and maximal use of thereown theoretical assessment and pratical advantages. Experiences from Korea, Taiwan, China and other countries emphasis the necessity of innovation in linkage of science-technology and economics for developing countries. Code: 19112601